Production response of Etawah cross breed (PE) doe due to improvement of feeding management during late pregnancy and lactation period - Dwi Yulistiani; I-W Mathius; I-K Sutama; Umi Adiati (Jurnal Ilmu Ternak dan Veteriner, 1999)
An experiment was caried out to study the protein requirement for Etawah cross breed. Thirty Etawah cross breed does were used in this study (average body weight 37.6+3.5 kg) and randomized to obtain one of three treatments. The treatments were the protein content of concentrate supplement. The protein levels were R1 (CP 16%), R2 (CP 22%) and R3 (CP 26%). The concentrate supplements were offered during late pregnancy and early (first 3 months) lactation period. The study showed that dry matter intake during pregnancy and early lactation period was not affected by treatments. The highest average daily gain during late pregnancy reached by R3 (66.45 g/day) which was not significantly different with R2 (61.9 g/day) and R1 (48.8 g/day). The highest total birth weight per does was achieved by R2 (6.05 kg). Average daily milk production was not affected by treatment. The production at first week of lactation was 1,044.5 g/day and decreased to 466.7 g/day in week 11. R2 produced the highest average daily gain (107.8 g/day) preweaning per does, while R1 and R3 was 84 and 84.4 g/day, respectively.   Key words : Etawah cross breed (PE), pregnancy period, lactation period, protein levels